Christian Leaders Who Want To Change: Self-Reformation As The Key To Effective Leadership - Wiki Purnama Gulo; Claudia Angelina (STT Transformasi Indonesia Manado, 2026)
This research examines the challenges of Christian leadership in the information age, an era characterized by rapid information flow, public scrutiny, and increasing demands for transparency and accountability. In such a context, leaders are expected not only to demonstrate competence but also to maintain strong moral integrity. The primary issue addressed in this study is the growing crisis of trust among followers, which often arises when leaders fail to live consistently with the ethical and spiritual values they proclaim. This research employs a qualitative method using a library research approach. Data were collected through an in-depth analysis of biblical texts, scholarly journals, and theological literature related to leadership principles. The findings reveal that personal renewal and self-reform, particularly by modeling leadership patterns rooted in the teachings and example of Christ, are essential for restoring credibility. Leadership strategies that emphasize humility, service, and consistency of character prove effective in rebuilding trust, strengthening community relationships, and inspiring renewed motivation among members within Christian organizations.